Rancang Bangun Aplikasi Berbasis Website Administrasi Surat Perintah Perjalanan Dinas Driver: Studi Kasus: PT PLN (Persero) UP3 Samarinda - Wahyudi Yulyanto; Syandy Apriyan Nur; Wawan Joko Pranoto (Pusat Riset dan Inovasi Nasional, 2024)
Official travel managers must reopen documents that have been archived if they need to get an official travel report within one month because this results in the system being less effective and efficient both in terms of material and time. If official travel data is lost or damaged due to poor storage processes and making official travel reports which takes quite a long time, the document must be reopened.